Pandawars Game Edukasi Pewayangan Berbasis Android - Nafis, Muhammad Rizqa; Yudantoro, Tri Raharjo; Sukamto, Sukamto (Teknik Elektro - Politeknik Negeri Semarang, 2017)
In 1960-1990, culture of wayang was idolized for every people, old, young, women, man, even childrens in Indonesia. But as time passed, wayang culture heritage decreased its fans number, because replaced with entertain-purpose media which more variative. As âPANDAWARSâ game edukasi pewayangan berbasis android was built, hopefully can can increase the attraction of people especially Elementary Student in wayang which ever became idol in interesting and entertaining ways. Method to built this Final Project was using Waterfall method. This model using a systematical order start from analysis, design, coding, testing, then operation and maintenance. After testing the application on 3 android devices, the application proved can functionally operated. Then the application was tested on 20 person and the result given is 83,57 % of userâs satisfaction, that means this application was very satisfying and hopfully can be used as the purpose of this application was built.Keywords : android, construct2, pandawa, wayang